Pengaruh Dukungan pada Perempuan Penderita HIV di Kota Jambi Tahun 2022 - Imat Rahmatilah; Najmah Najmah; Nur Alam Fajar (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Human Immunodeficiency Virus (HIV) is a retrovirus that belongs to the lentivirus family. HIV causes some damage to the immune system and destroys it. Acquired Immunodeficiency Syndrome (AIDS) is a collection of symptoms and infections that arise due to damage to the human immune system due to infection with the HIV virus. AIDS is defined as the most severe form of persistent illness associated with HIV infection. The neglect of women's reproductive health rights related to HIV testing is an obstacle to accessing HIV services. This situation causes women with HIV to enter into a bad condition physically and psychologically so that good resilience is needed so that these HIV-infected women can continue their lives without heavy mental stress. This study aims to in-depth look at the effect of providing support to women living with HIV in Jambi City using a qualitative research design with data collection techniques and in-depth interviews. This study involved 6 key informants with an age distribution of 31 to 47 years. The results showed that women living with HIV in Jambi City experienced physical and psychological disorders, they need to get attention and support from family, friends and companions as well as health workers.